Studies on the chemical compatibility of soil-bentonite cut-off walls for landfills. (1st May 2019) - Xu, Haoqing; Shu, Shi; Wang, Shengwei; Zhou, Aizhao; Jiang, Pengming; Zhu, Wei; Fan, Xihui; Chen, Liang
Abstract: Leachate contains composite contaminants, and the chemical compatibility of soil-bentonite cut-off walls is unclear. To better understand the issue, Fujian standard sand is used to represent a sandy soil stratum. Two clays were used as additive to examine the chemical compatibility of the soil-bentonite model backfills under the condition of composite contaminants. The results indicate that there is a representative cation when the backfills are permeated with NaCl, CaCl2, and ZnCl2 solutions and an NaCl-CaCl2 -ZnCl2 mixed solution of the same ionic strength. Ca 2+ has the highest maximum ionic strength among all cations from leachates. Moreover, the change in hydraulic conductivity, bound water content and effective porosity of sand-bentonite with the Ca 2+ concentration or chemical oxygen demand (COD) exhibit a concentration threshold; i.e., when the concentration is smaller than the threshold, the hydraulic conductivity and effective porosity significantly increase, whereas the bound water content rapidly decreases; when the concentration is higher than the threshold, the hydraulic conductivity, bound water content and effective porosity tend to stabilize. In addition, under the condition of composite contaminants, the threshold is observed, while the hydraulic conductivity, bound water content and effective porosity vary with the COD. Thus, both the type and concentration of chemicals can change the effective porosity and affect hydraulic conductivity. Furthermore, there is a power function relationship between permeability and the effective pore. Highlights: The representative cation under multispecies cation was clarified. A concentration threshold was discovered.